Resolutions of the Kentucky legislature, on the subject of abolition (House document (Virginia. General Assembly. House of Delegates) ;, 1836)
1836 Resolutions of the Kentucky General Assembly transmitted by Virginia Governor Tazewell to the Virginia House of Delegates. Included were resolutions which reaffirmed states' rights to control domestic slavery; against abolition societies and Congress' attempt to prohibit slavery in the District of Columbia, and the support of Kentucky to those ends.